Comparison of reading performance with low add bifocal and extended depth of focus intraocular lenses implanted with mini-monovision - TOKER, AYŞE EBRU; SEVİK, MEHMET ORKUN; AKKAYA TURHAN, SEMRA (SPRINGER, 2021)
Purpose To evaluate reading performance, preferred reading distance, and spectacle independence in patients implanted with a low add multifocal or an extended depth of focus (EDOF) intraocular lens (IOL) after phacoemulsification. Methods In this prospective study, patients were randomized into two groups: the diffractive multifocal Tecnis + 2.75 D (ZKB00) IOL (Tecnis + 2.75 group; 15 patients) or the EDOF Tecnis Symfony (ZXR00) IOL (Symfony group; 14 patients) for bilateral implantation with mini-monovision. Reading performance parameters (reading acuity [RA], critical print size [CPS], and maximum reading speed [MRS]) were evaluated with MNREAD acuity charts at 40 cm, and preferred reading distances and spectacle independence for near activities were assessed preoperatively and at the postoperative 1st, 3rd, and 6th months. Results At the postoperative 6th month, binocular logMAR UNVA and DCNVA were significantly better in the Symfony group than in the Tecnis + 2.75 group (UNVA: 0.15 +/- 0.07 vs. 0.22 +/- 0.08,p = 0.046; DCNVA: 0.21 +/- 0.05 vs. 0.28 +/- 0.07,p = 0.043; respectively). There was no significant difference in reading performance parameters between the groups; however, the Symfony group preferred significantly closer reading distance than the Tecnis + 2.75 group (42.00 +/- 4.67 cm; 45.87 +/- 5.32 cm, respectively,p = 0.030). At the postoperative 6th month, 14.3% and 26.7% of patients reported that they needed spectacles, rarely or occasionally, for near activities in the Symfony and Tecnis + 2.75 groups, respectively (p > 0.05). Conclusions When implanted with mini-monovision, although functional near visual acuity and a high degree of spectacle independence at near distances were achieved with both IOLs, patients implanted with the EDOF IOL preferred closer reading distance than those implanted with the low add diffractive multifocal IOL.
Keywords: Extended depth of focus; Mini-monovision; Reading performance; VISUAL OUTCOMES; BILATERAL IMPLANTATION; PATIENT SATISFACTION; CONTRAST SENSITIVITY; CLINICAL-EVALUATION; RANGE; VISION; ACUITY; QUALITY; EYES